A SEGURANÇA DO TRABALHADOR NA CONSTRUÇÃO E MONTAGEM DE UNIDADES INDUSTRIAIS VISTA NA FASE DE PROJETO - Cruz, Francisco Santos (2004)
The number of work accidents in the construction and assembly industry is very high in Brazil and in the world. It is recognized internationally that this industry type is very late in relation to others industries with relationship to turn the workplace safe for the workers. One in the ways of providing larger safety to the workers during the construction and assembly phase is to eliminate or to minimize the risks still in the design phase. The presented work gives a general vision of work accidents in the construction and assembly industry and it details how is the situation of the consideration of the worker's safety aspects responsible for the execution of the work still in the design phase. A rising of data was accomplished with the design community regarding great projects of the petroleum industry, where the themes training and the designers' culture were approached in relation to the consideration of the worker s safety aspects through the design, being reached the conclusion that in both cases the concern with that subject is still very low. For the two approached themes a correlation was made with the Accidents with Lost Time Rates (TFCA) of the enterprises, being observed that there is a tendency of fall of that rate in the projects in that the safety through the design is more disseminated.